2005
DOI: 10.1111/j.1468-3083.2005.01144.x
|View full text |Cite
|
Sign up to set email alerts
|

Has Helicobacter pylori eradication therapy any effect on severity of rosacea symptoms?

Abstract: References1 Friboes W. Beitrag zur Klinik und Histopathologie der gutartigen Hautepitheliome . S. Karger-Verlag, Berlin, 1912. 2 Kleine-Natrop HE. Simultaneous generalization of benign basalioma of both Spiegler and Brooke types. Arch Klin Exp Dermatol 1959; 209 : 45 -55. 3 Volter C, Baier G, Schwager K et al. Cylindrocarcinoma in a patient with Brooke-Spiegler syndrome. Laryngorhinootologie 2002; 81 : 243 -246. 4 Durani BK, Kurzen H, Jaeckel A et al. Malignant transformation of multiple dermal cylindromas. Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 6 publications
2
17
0
3
Order By: Relevance
“…17 Furthermore, the increased prevalence of HPI is reasonably well established and although the risk of new-onset HPI was not increased among patients with rosacea, the baseline prevalence of HPI was significantly higher (P < 0Á001) among patients with rosacea. 12,14,[29][30][31][32][33][34][35] Lastly, the association between rosacea and IBS has not been previously reported, but is in accordance with the complaints (in particular a bloated feeling) that we frequently hear from our patients with rosacea. However, we cannot exclude that some patients may have been incorrectly diagnosed with IBS as they may instead have been suffering from one of the other studied conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…17 Furthermore, the increased prevalence of HPI is reasonably well established and although the risk of new-onset HPI was not increased among patients with rosacea, the baseline prevalence of HPI was significantly higher (P < 0Á001) among patients with rosacea. 12,14,[29][30][31][32][33][34][35] Lastly, the association between rosacea and IBS has not been previously reported, but is in accordance with the complaints (in particular a bloated feeling) that we frequently hear from our patients with rosacea. However, we cannot exclude that some patients may have been incorrectly diagnosed with IBS as they may instead have been suffering from one of the other studied conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the observed significant association between rosacea and CeD is in agreement with one recent GWAS study that showed shared genetic risk loci for these two conditions . Furthermore, the increased prevalence of HPI is reasonably well established and although the risk of new‐onset HPI was not increased among patients with rosacea, the baseline prevalence of HPI was significantly higher ( P < 0·001) among patients with rosacea . Lastly, the association between rosacea and IBS has not been previously reported, but is in accordance with the complaints (in particular a bloated feeling) that we frequently hear from our patients with rosacea.…”
Section: Discussionsupporting
confidence: 91%
“…1348 Acne rosacea has been reported in patients with HIV infection. [1358][1359][1360][1361][1362][1363] A rosacea-like eruption has also occurred with Candida albicans infection. [1355][1356][1357] It is likely that the treatment used for H. pylori is beneficial for rosacea.…”
Section: Keratosis Follicularis Spinulosa Decalvansmentioning
confidence: 99%
“…Improvment in the symptomatology of the disease noticed after the treatment of HP infection is supported by several studies, while other authors consider that this treatment and RS evolution are not connected (8,9). Some authors go even further and claim that RS is in fact an extragastric manifestation of HP infection (2,10,11).…”
Section: Results Resultsmentioning
confidence: 70%